Culture industry: genesis and significance of a critical concept - Maiso, Jordi (Escritura e Imagen, 2018)
The present paper aims at reappropriating the critical potential of the critique of the culture industry for the analysis of contemporary society. The term “culture industry” was coined in the Dialectic of Enlightenment, and the attempt is both to understand its significance in the midst of the 20th Century and its possible validity today. Firstly the paper sketches what is at stake in Theodor W. Adorno’s analysis, attempting to clarify some of the most wide-spread missunderstandings in its reception. For Adorno, culture industry was above all a crucial concept in order to comprehend the transformations of capitalism in its post-liberal stage. Later on, the paper attempts to reappropriate this analysis in order to illuminate contemporary phenomena. The attempt is to update the critical diagnostic of the culture industry in the light of the current processes of digitalization, virtualization of the lifeworld and transformation of the labor relations. This aims at an understandig of the actual relations between socialization, culture and the living conditions.